Phase Transitions and Microstructural Processes in Shape Memory Alloys - Adiguzel, Osman (Trans Tech Publications Ltd, 2013)
Shape memory alloys exhibit a peculiar property, shape memory effect that is the result from the structural changes in microscopic scale. These alloys return to previously defined shapes when they are subjected to variation of temperature after deformation of the low temperature phase. Shape-memory effect is based on martensitic transformation, with which the material changes its internal crystalline structure. The ordered structure or super lattice structure is essential for the shape memory effect of the material. Copper based alloys exhibit this property in the beta- phase field, which possesses the simple bcc-structure at high temperature austenite phase. As the temperature is lowered, austenite phase undergoes martensitic transition following two ordering reactions, and microstructural changes in microscopic scale govern this transition. In the present work, Cu alloys were investigated by transmission electron microscope, TEM, and x-ray diffraction techniques.
7th International Conference on Physical and Numerical Simulation of Materials Processing (ICPNS 2013) -- JUN 16-19, 2013 -- Oulu, FINLAND
Keywords: Martensitic transition; shape memory effect; twinning; detwinning layered structures; martensite stabilization